Everyone happy: Living standards in Germany 25 years after reunification - Maximilian Priem; Jürgen Schupp (DIW Economic Bulletin, 2014)
It is now a quarter of a century since the fall of the Berlin Wall and the gap in living standards between eastern and western Germany is still not fully closed. Admittedly, this could not realistically have been expected. Despite the increase in life satisfaction in eastern Germany, the east-west divide prevails. Evidence of this can be found in the latest data from the long-term Socio-Economic Panel (SOEP) study gathered by DIW Berlin in cooperation with the fieldwork organization TNS Infratest Sozialforschung. According to the SOEP data, in 2013, eastern Germans were far less happy than western Germans, although the level of life satisfaction in the east was higher than at any other point in the history of the survey, which was conducted for the first time in eastern Germany in 1990-shortly before economic, currency, and social union. Other subjective indicators reveal differences in satisfaction with household income, health, and childcare. In contrast, job satisfaction, as well as satisfaction with housing, housework, and leisure time have converged. Eastern Germans worry more about crime levels and their own financial circumstances, whereas concerns about xenophobia and employment have diminished throughout Germany. The SOEP surveys show that, according to population, living standards in Germany are now largely aligned. Despite a number of specific problems which, in the coming years, will include the development of new pensions in eastern Germany in particular, German reunification has proven to be an extraordinary success story.
Keywords: Z10; 330; German Unification; Satisfaction; Well-Being; SOEP